Acute Kidney Injury Induced Lupus Exacerbation Through the Enhanced Neutrophil Extracellular Traps (and Apoptosis) in Fcgr2b Deficient Lupus Mice With Renal Ischemia Reperfusion Injury - Saisorn, Wilasinee; Saithong, Supichcha; Phuengmaung, Pornpimol; Udompornpitak, Kanyarat; Bhunyakarnjanarat, Thansita; Visitchanakun, Peerapat; Chareonsappakit, Awirut; Pisitkun, Prapaporn; Chiewchengchol, Direkrit; Leelahavanichkul, Asada (Frontiers in Immunology, 2021)
Renal ischemia is the most common cause of acute kidney injury (AKI) that might be exacerbate lupus activity through neutrophil extracellular traps (NETs) and apoptosis. Here, the renal ischemia reperfusion injury (I/R) was performed in Fc gamma receptor 2b deficient (Fcgr2b-/-) lupus mice and the in vitro experiments. At 24 h post-renal I/R injury, NETs in peripheral blood neutrophils and in kidneys were detected using myeloperoxidase (MPO), neutrophils elastase (NE) and citrullinated histone H3 (CitH3), as well as kidney apoptosis (activating caspase-3), which were prominent in Fcgr2b-/- mice more compared to wild-type (WT). After 120 h renal-I/R injury, renal NETs (using MPO and NE) were non-detectable, whereas glomerular immunoglobulin (Ig) deposition and serum anti-dsDNA were increased in Fcgr2b-/- mice. These results imply that renal NETs at 24 h post-renal I/R exacerbated the lupus nephritis at 120 h post-renal I/R injury in Fcgr2b-/- lupus mice. Furthermore, a Syk inhibitor attenuated NETs, that activated by phorbol myristate acetate (PMA; a NETs activator) or lipopolysaccharide (LPS; a potent inflammatory stimulator), more prominently in Fcgr2b-/- neutrophils than the WT cells as determined by dsDNA, PAD4 and MPO. In addition, the inhibitors against Syk and PAD4 attenuated lupus characteristics (serum creatinine, proteinuria, and anti-dsDNA) in Fcgr2b-/- mice at 120 h post-renal I/R injury. In conclusion, renal I/R in Fcgr2b-/- mice induced lupus exacerbation at 120 h post-I/R injury partly because Syk-enhanced renal NETs led to apoptosis-induced anti-dsDNA, which was attenuated by a Syk inhibitor.